Slovenia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in Slovenia during 1990-96. Slovenia experienced its first positive real GDP growth in 1993. Real GDP grew by 1.3 percent. This modest recovery began under the impetus of buoyant domestic demand, which grew by 8u percent; real foreign demand contracted by 6 1\2 percent owing to a recession in Western markets. Despite the growth in real aggregate demand by more than 2 percent, the output response was dampened as domestic demand growth spilled primarily into a boom in consumer goods imports.